Recent Progress in Microfiltration/Ultrafiltration Membranes for Separation of Oil and Water Emulsions. Issue 7 (21st February 2022) - Baig, Nadeem; Salhi, Billel; Sajid, Muhammad; Aljundi, Isam H.
Abstract: Oily wastewater has become one of the leading causes of environmental pollution. A massive quantity of oily wastewater is released from industries, oil spills, and routine activities, endangering the ecosystem's sustainability. Due to the enormous negative impact, researchers put strenuous efforts into developing a sustainable solution to treat oily wastewater. Microfiltration/ultrafiltration membranes are considered an efficient solution to treat oily wastewater due to their low cost, small footprint, facile operation, and high separation efficiencies. However, membranes severely fouled during the separation process due to oil's adsorption and cake layer formation, which shortens the membranes' life. This review has critically discussed the microfiltration/ultrafiltration membrane synthesizing methods and their emulsion's separation performance. In the end, key challenges and their possible solutions are highlighted to provide future direction to synthesize next‐generation membranes. Abstract : In this account review, we have discussed the oil/water separation by using the membranes. Ceramic and polymeric membranes are summarized for their application to treat oily wastewater. The major challenges in membranes‐based separation processes are also discussed.